The Design of Wireless Medical Devices with Multi-sensor Using Android and iOS-Based Smartphone Displays - Ade Handayani; Mutiara Amanda; M. Zakuan Agung; Nyayu Latifah Husni; Hertanti Indah Lestari; Moh Heri Kurniawan; Mega Hasanul Huda (Jurnal E-Komtek, 2022)
In this study, a multisensor wireless medical device was designed using several sensors, such as body temperature, oxygen levels, blood pressure, and heart rate, that connects to the application and applies WBAN technology. The design of this tool applied the principle of IoT, where a system that can monitor body health is needed, a remote monitoring system on the smartphone. The data obtained by the tool is sent to the server to be later forwarded to the application. In this study, Fuzzy Mamdani's method was used to implement the health status. The IoT principle makes it effortless for users to access or use pre-designed tools. Therefore, in this study, the IoT principle is employed to make it more efficient and easier for users to read the results because the data will be forwarded to applications installed on users' smartphones, both Android and iOS-based.